The Martyr Archetype And A Brief History Of The Electric Chair In Frank Darabont’s ‘The Green Mile’ - Thapliyal, Nehal; Gupta, Divya (Journal of Neonatal Surgery, 2025)
Stephen King's The Green Mile[i], originally published on August 29, 1996, was chosen by Frank Darabont for film adaptation, which resulted in the film's first premier with the same title, the Green Mile, on December 10, 1999[ii]. The Film is an American fantasy drama that deals with various aspects of the Great Depression. It deals with religious matters, crime, racism, death row, and execution through the electric chair. This article aims to analyze the incidents of wrongful execution by the electric chair during the late 19th and early 20th century and the pain and suffering of the martyr archetype (John Coffey) as described in the film.